Evaluation of agronomic performances of rainfed barley double-haploids (DHs) lines under semi-arid conditions - LARBI KARKOUR; MOHAMMED FENNI; DALILA RAMLA; DJOUHER GAAD; ABDELKADER BENBELKACEM (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Karkour L, Fenni M, Ramla D, Gaad D, Benbelkacem A. 2019. Evaluation of agronomic performances of rainfed barley double-haploids (DHs) lines under semi-arid conditions. Biodiversitas 20: 1398-1408. Sixty-six doubled-haploid (DHs) barley lines derived from F2 plants of three bi-parental single crosses, between the local variety (Tichdrett) and three introduced genotypes (Express, Plaisant, and Exito) were evaluated in 2017 for agronomic performance. The experiment was undertaken at two locations under rainfed conditions in semi-arid zone of Algeria in a randomized block design with three replications. Each line was scored for fifteen quantitative traits: number of days to heading, thousand grains weight, number of grains per spike, spikes number per m2, plant height, spike length, leaf relative water content, awn length, peduncle length, spike weight, grain weight per spike, leaf area, specific leaf weight, grain yield and harvest index. The results indicated that the presence of highly significant genotype effect for all traits except for leaf area and highly significant environment effect for all characters, except spikes number per m2and awns length. Genotype x environment interaction was highly significant for all traits, except specific leaf weight and leaf area. Significant positive correlation between the twelve agronomic traits, ranging from 0.45 to 0.87, were observed among the number of grains per spike, thousand grains weight, the number of spikes per m2, yield of grains and harvest index. The principal component analysis showed that four components could describe 72% of total variances. Cluster analysis divided all genotypes studied into three cluster groups. Overall, results of agronomic parameters and those related to the biotic and abiotic stresses will be used for better identifying this germplasm and better-directing studies of genetic improvement.